Manajemen ZIS (Zakat, Infaq, Shodaqoh) di Masjid Nurul Huda Desa Ngimbang Palang Tuban - Nurul Istiqomah; Sutopo Sutopo; Risma Damayanti (Al-Muzdahir : Jurnal Ekonomi Syariah, 2022)
Seeing the considerable potential of ZIS at the Nurul Huda Mosque, the mosque administrators formed a management to make it easier to distribute ZIS funds to worshipers and people in need. Therefore, it is hoped that more and more mosques will establish Baitul Maal as a positive response to mosques in the development of the times so that they can prepare generations of nations who can manage and distribute ZIS funds properly and effectively with strong religious provisions. This research was conducted at the Nurul Huda Mosque, Ngimbang Village, Palang District, Tuban Regency with the aim: to find out how ZIS management (Zakat, Infaq and Shadaqoh) and the inhibiting and supporting factors for ZIS management (Zakat, Infaq and Shodaqoh) at the Nurul Huda mosque, Ngimbang Village, Palang District Tuban Regency. This research uses a descriptive approach which is a research method that describes the circumstances or situations that occur, so that the data collected is in the form of words and pictures. The results of this research are Zakat, infaq and shodaqoh funds that have been collected and then distributed to the people who are blessed to receive, the distribution is carried out twice a year, namely during the Eid al-Fitr and Eid al-Adha holidays. The inhibiting factor for the management (ZIS) of zakat, infaq and shodaqoh at the Nurul Huda Mosque, Ngimbang Palang Tuban Village, is the lack of validity of the data that goes to the mosque administrators. Factors supporting the management (ZIS) of zakat, infaq and shodaqoh at the Nurul Huda Mosque, Ngimbang Palang Tuban Village, are trust from the community to manage funds that have been submitted to the mosque, optimism in carrying out tasks and mandates, and working with religious leaders and also the chaplain.